Leadership styles of the directors of the public institutions of Tingo María, 2018 - Herrera-Alania, Gladys (2020)
The objective was to describe the leadership styles exercised by the directors of Public Institutions of Tingo María, 2018. Methods: It was a study with a quantitative, prospective, observational, cross-sectional and descriptive approach, with a non-experimental design. The population was made up of 132 executives of the public institutions of Tingo María, from which they were selected by simple random probability sampling, using the formula for the finite population, where a total of 98 executives was obtained, a guide was used in data collection of interview of general characteristics and questionnaire of styles of Leadership of the directors of the institutions, previously validated and reliable, by eight experts in the area and its reliability reached a Cronbach's alpha coefficient r = 0.85. Ethical considerations for research were applied. The data were analyzed applying descriptive and inferential statistics. In the results, transactional leadership had a high weighted average (4.0); being the direction indicator by exception the one with the greatest influence with 4.08 points; followed by transformational leadership with a (3.99) weight average, where the inspiration indicator with (4.12) points has achieved better results in the commitment to the organization and the achievement of goals in the staff and a low average with ( 3.97) in instructional leadership, whose professional development indicator with (4, 16) points managed to enhance the capacities of the members of the institutions. Therefore, it was concluded that the transactional style is the leadership that is mostly applied by the directors of the public institutions of Tingo María.